2020
DOI: 10.1111/acfi.12722
|View full text |Cite
|
Sign up to set email alerts
|

Economic policy uncertainty exposure and earnings management: evidence from China

Abstract: We investigate the impact of economic policy uncertainty (EPU) exposure on the earnings management behaviour of Chinese firms. We find a significantly positive relation between EPU exposure and firms’ earnings management. In addition, the EPU exposure effect is more pronounced for firms with weaker external monitoring mechanisms. We also find that the financial leverage and growth rate of individual stocks have significant predictive ability for EPU exposure. When we examine the potential mechanisms linking EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 104 publications
(212 reference statements)
9
44
1
Order By: Relevance
“…Accordingly, Ghosh and Olsen (2009) use the coefficients of variation for sales and analyst forecast dispersion to measure firm-level environmental uncertainty and find that the magnitude of discretionary accruals is higher with uncertainty. Cui et al (2020) yield similar results, the difference being that firms' exposure to environmental uncertainty is based on the Economic Policy Uncertainty (EPU) Index constructed by Davis et al (2019). Using the implied volatility of equity options as the proxy for firmlevel uncertainty, Stein and Wang (2016) go a step further and investigate the impact of uncertainty on the earnings management direction, rather than just the magnitude.…”
Section: Environmental Uncertainty and Earnings Managementmentioning
confidence: 69%
“…Accordingly, Ghosh and Olsen (2009) use the coefficients of variation for sales and analyst forecast dispersion to measure firm-level environmental uncertainty and find that the magnitude of discretionary accruals is higher with uncertainty. Cui et al (2020) yield similar results, the difference being that firms' exposure to environmental uncertainty is based on the Economic Policy Uncertainty (EPU) Index constructed by Davis et al (2019). Using the implied volatility of equity options as the proxy for firmlevel uncertainty, Stein and Wang (2016) go a step further and investigate the impact of uncertainty on the earnings management direction, rather than just the magnitude.…”
Section: Environmental Uncertainty and Earnings Managementmentioning
confidence: 69%
“…Compared with other market participants, the firm's managers have more specific and correct predictions about the impact of external policy changes on the firm, which means that information asymmetry exists between the two parts [7]. So Cui, Yao, Fang, et al [8] suggest that firms need to use more accounting conservatism to solve the problems caused by policy uncertainty. [9] Chen and Chen found that the instability of economic policies, like the province government leader's change, makes companies with high-profit accounting information subject to social suspicion and unfavorable behavior of the government.…”
Section: The Relationship Between Economic Policy Uncertainty and Earnings Managementsmentioning
confidence: 99%
“…In addition, if economic policy uncertainty causes the firm to face greater government-related economic transfers such as increases of tax or tariff, the firm chooses to use accounting procedures to employ earnings management to reduce the cost of increased government regulation. Like those in China, under China's economic policy and political system, economic policy uncertainty growth drives an increase in earnings management behavior, especially companies that have less monitoring outside [8]. Under these circumstances, people also need to realize that the positive relationship of economic policy uncertainty on corporate earnings management is also related to the intensity of uncertainty, which is then influenced by the quality of government and the dependence between enterprises and government [9].…”
Section: The Relationship Between Economic Policy Uncertainty and Earnings Managementsmentioning
confidence: 99%
See 1 more Smart Citation
“…China's capital market provides a good case study for examining this issue. First, since the Chinese stock market is still a developing market, listed companies are plagued by serious agency problems, including earnings management (Jiang et al, 2010;Cui et al, 2020), related party transactions (Berkman et al, 2010;Shen et al, 2019) and financial fraud (Liao et al, 2019;Zhou et al, 2020). Second, retail investors in the Chinese stock market have become the main force dominating the Chinese stock market.…”
Section: Introductionmentioning
confidence: 99%